Research of fluid flow in two-dimensional and three-dimensional formulation in the flow part of a high-pressure francis turbine - Mironov, Konstantin Anatolievich; Oleksenko, Yuliia Yuriivna (Національний технічний університет "Харківський політехнічний інститут", 2019)
The paper presents some results of a computational study of the spatial flow of a viscous fluid in a high-pressure Francis turbine Fr500 (in the optimal mode). To improve the energy performance at the preliminary design stage of the turbine, numerical flow simulations should be carried out. The difficulty of solving the problem posed is due both to the complex spatial geometry of the blade system of the runner and the varying degree of influence of the working bodies on the formation of energy characteristics. This CFD approach reduces costs and time in comparison with the experimental approach and makes it possible to improve and analyze turbine performance and its design before the model is manufactured. The computational complex of programs provides an opportunity to see the picture of pressure distribution, the field of velocity vectors and the movement of fluid particles for substantiation and analysis of results. Numerical modeling of the spatial flow in the flow part of the turbine was carried out to determine changes in the energy characteristics, therefore, the k - ε turbulence model was chosen, this model is the most successful model of first-level turbulence of the circuit. The results of the computational study confirm that the hydraulic efficiency of a hydraulic turbine largely depends on the losses in the guide vane and the runner, which means it is these elements that should be given the most attention, their design and coordination of the flow in them. Analysis of the energy loss in the flow part of the Francis turbine was carried out using programs for calculating fluid flow in two-dimensional and three-dimensional formulation. The obtained calculated data correspond to the previously known experimental recommendations for high-pressure Francis turbine. The issues of increasing the energy performance of a projected high-pressure Francis turbine were considered.

В роботі представлені деякі результати розрахункового дослідження просторової турбулентної течії в'язкої рідини в проточній частині високонапірної радіально-осьової гідротурбіни РО500. Для поліпшення енергетичних показників на попередньому етапі проектування гідротурбіни проводиться чисельне моделювання потоку. Складність вирішення поставленого завдання обумовлена як складної просторової геометрією лопатевої системи робочого колеса, так і різним ступенем впливу робочих органів на формування енергетичних характеристик. Даний підхід CFD знижує витрати і час в порівнянні з експериментальними підходом і дає можливість удосконалити і аналізувати показники турбіни і її конструкцію до моменту виготовлення моделі. Розрахунковий комплекс програм надає можливість побачити картину розподілу тиску, поле векторів швидкості і руху частинок рідини для обґрунтування та аналізу результатів. Чисельне моделювання просторового потоку в проточній частині гідротурбіни було проведено для визначення зміни енергетичних характеристик, тому була обрана k - ε модель турбулентності, дана модель є найбільш вдалою моделлю турбулентності першого рівня замикання. Наведені результати розрахункового дослідження підтверджують, що гідравлічний коефіцієнт корисної дії гідравлічної турбіни в значній мірі залежить від втрат в напрямному апараті і робочому колесі і означає саме цим елементам варто приділяти найбільші увагу, їх конструкції та узгодженню потоку в них. Аналіз втрат енергії в проточній частині радіально-осьової гідротурбіни був проведений з використанням програм для розрахунку течії рідини в двовимірній і тривимірній постановці. Отримані розрахункові дані відповідають відомим раніше експериментальним рекомендаціям для високонапірної радіально-осьової гідротурбіни. Були розглянуті питання підвищення енергетичних показників спроектованої високонапірної радіально-осьової гідротурбіни.
Дослідження потоку рідини в двовимірній і тривимірній постановці в проточній частині високонапірної радіально-осьової гідротурбіни
Keywords: spiral case; guide vanes; draft tube; CFD; спіральна камера; напрямний апарат; відсмоктуюча труба; CFD